The Development of Indigenous People Rights to Their Land Through Political Participation and International Norm in Latin America - Pratiwi, Tiffany Setyo (Program Studi Hubungan Internasional, 2017)
AbstractThis paper will explain about how indigenous people as minority group receive their recognition and accommodation by government, especially in implementation of international norm that pertains to indigenous peoples and recognized in the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and Convention ILO 169. This paper will explore the issue in Latin Amerika region. To achieve the objective of this paper, author will explain in two main themes: First, the development of the political participation indigenous people in Latin American states. Second, the rights of indigenous people to their ancestral land through international norm FPIC (Free, Prior, and Informed Consent) that adopted in Latin America states. I argue that the development of indigenous people rights to their land in Latin America is supported by political participation of indigenous people in the government system in Latin America states.